Współczesne metody filologiczne w interpretacji żydowskich dokumentów osobistych - Ewa Geller (Autobiografia, 2017)
When using traditional life writing as source for scholarly research, one usually applies either the biographical or the philological method of analysis. For a researcher of the history of Polish Jews obtaining and deciphering such documents is already a challenging task; he or she should however choose and consciously apply just one of the above-mentioned methods in order to support any conclusions drawn from single life stories and any generalizations regarding the times, places, cultural phenomena and choices of the social groups in question. This paper describes the philological method’s principles and scope in relation to Karl Bühler’s classic Organon Model. It also presents several modern tools used in text linguistics and discourse analysis, all of which broaden the traditional understanding of the philological method thereby allowing a more objective interpretation of life writing practices.